Attributions of Criminal Responsibility of Children : An Exploratory Study of the Role of Wrongdoer age, Victim Harm and Perceptions of Intent and Consequence - McCue, James (2003)
Recent cases, such as that of James Bulger, have provided anecdotal evidence of children's capacities to commit illegal acts. Currently however, the public's attributions of children who engage in antisocial and criminal behaviour, and whether they should be held criminally responsible for their actions, has received little attention in terms of empirical research. The aim of the present study was to examine these attributions and establish whether they concur with the guidelines for criminal responsibility set down by the Western Australian criminal justice system. Two independent variables were manipulated using vignettes and included the age of the wrongdoer (7, 10 or 14 years of age) and the consequence, or harm, caused to the victim (no physical consequence, moderate physical consequence or extreme physical consequence), thus meaning there were nine experimental conditions in total. One hundred and eighty university students participated in this exploratory research and each participant was required to read a vignette and then fill in an eight-item questionnaire that measured their perceptions of the scenario, depicted using a seven-point Likert scale. A qualitative measure was also included to supplement the quantitative data in terms of how the public believed the wrongdoer should be dealt with. Results indicated that the consequence to the victim significantly influenced perceptions of the harmfulness of the wrongdoer's behaviour, perceptions of the severity of the harm and perceptions of whether the wrongdoer should be dealt with by the justice system. The age of the wrongdoer did not significantly influence any of the variables measured. Perceptions of responsibility, intent and behavioural severity were influenced by contextual factors related to the vignette presented. Overall it was found that the public do believe children should be held responsible for their actions. However, results showed that the wrongdoer should be dealt with according to the contextual circumstances of the act, rather than applying punitive justice system punishments. The results ultimately highlight a disparity in the perceptions of the public and the current legislation of the Western Australian Criminal Code. These results are discussed in relation to previous research and implications for the Western Australian criminal justice systems are also presented